Management decision support by managerial games - Horčička, Aleš (Univerzita Pardubice, 2007)
Decisions are occurring in our every-day-life more as we imagine, many decisions are often made without thinking for a long time about it. But a decision can also be more complex, it starts with a difficult personal decision where one has to weigh the outcomes of each alternative until decisions in big organizations which are made for many more than only one individual and which will affect in some cases whole communities or countries. As you can see, there are many dimensions of decisions and how to meet them. The aim of the essay is to describe first the most common decision making theories and then show some examples of different situations.
Keywords: Management; decision making; management decisions; decision support; managerial games